Penerapan Media Pembelajaran Berbasis Google Site dalam Upaya Peningkatan Hasil Belajar pada Mata Pelajaran Sosiologi di Kelas XI IPS 2 SMA Negeri 1 Ampek Angkek - Rezka Nurliswati; Nurlizawati Nurlizawati; Annisa Citra Triyandra (Naradidik: Journal of Education and Pedagogy, 2022)
This article describes the application of Google Sites based learning media in an effort to improve learning outcomes in Sociology subjects in class XI IPS 2 SMA Negeri 1 Ampek Angkek. The method used is the Classroom Action Research (CAR) method using the Contextual Teaching and Learning (CTL) model. In its application, all the steps needed in the contextual teaching and learning (CTL) model are carried out, namely modeling, inquiry, questioning, learning community, constructivism, reflection, and authentic assessment. The results of this study indicate that the application of Google Site based learning media can improve student learning outcomes. The learning media made consist of the Main Page, Absensi Page, Pre Test Page, material Page, feedback page, and Post Test Page. This media was validated by sociology teacher. The feasibility of Google Sites media is based on the score obtained for each aspect by sociology teachers to get an assessment result with an average score of 76 which is included in the appropriate category.